"I just might kill myself": Suicide expressions on Twitter. Issue 3 (3rd March 2020) - Spates, Kamesha; Ye, Xinyue; Johnson, Ashley
Abstract: In order to examine how Twitter can be a significant indicator of how suicidal thoughts occur and spread, we used content analysis to analyze 4524 Twitter messages. Although expressions of "wanting to die" occurred frequently, most of the tweets appeared to be non-threatening. In addition, discussions about suicide on Twitter mostly involved sharing suicide prevention resources with fellow users. This finding suggests that Twitter could offer an efficient way to circulate suicide awareness materials across geographical bounds.